Which is More Accurate in Measuring the Blood Pressure? A Digital or an Aneroid Sphygmomanometer - Bhaskar Shahbabu (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Hypertension is one of the major public health problem affecting the whole world so its accurate measurement is of utmost importance for its early diagnosis and management. Concerns related to the potential ill effects of mercury on health and environment, has led to the widespread use of non-mercury sphygmomanometers. Aim: A study was conducted to compare the accuracy of readings of aneroid and digital sphygmomanometers in reference to mercury sphygmomanometers and determine the hypertensive classification agreement between the mercury and non-mercury devices. Materials and Methods: The study was conducted in an OPD of a health centre in a rural community of West Bengal which is the rural field practice area of our institute. An aneroid and a digital sphygmomanometer were compared to a properly calibrated mercury sphygmomanometer. All the subjects above the age of 25 years, in two days per week, selected randomly from five working days per week in a period of one month were selected. Two blood pressure readings of each of 218 study subjects was recorded with each pretested sphygmomanometer. Paired t-test, Kappa coefficients, sensitivity and specificity tests were done. Receiver Operating Characteristics curve analysis was done and Youden index was estimated to detect the optimal cut off point for the diagnosis of hypertension by non-mercury sphygmomanometers. Results: Data analysis of 218 study subjects showed the mean difference of the mercury reading and the test device was much less for aneroid than that of the digital device for both systolic and diastolic blood pressure. More than 89% of aneroid readings and less than 44% of the readings by digital device had absolute difference of 5mm Hg. when compared with the mercury readings for both systolic and diastolic blood pressure. Sensitivity and specificity of aneroid device was higher (86.7% and 98.7%) than digital device (80% and 67.7%). Receiver Operating Characteristic curve had larger area under the curve for aneroid device than digital device for both SBP and DBP. Conclusion: The aneroid device had better accuracy than the digital device as compared to mercury sphygmomanometer and should be used for proper and better management.